Applicative Construction of Malay Sorkam Dialect - Luthvia Chairunnisa; Mulyadi (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This research examines applicative constructions in Sorkam Dialect Malay, which include benefactive, instrumental and locative types, and compares them with previous research to fill gaps in knowledge about regional language typology. Through qualitative descriptive methods, data is collected from daily conversations of native speakers, research articles, and data from other researchers. The results of the analysis show that benefactive applicative constructions are marked with the suffixes -kan and -i on transitive verbs, while instrumental applicative constructions mark instruments with the suffix -kan, and locative applicative constructions mark locations with the suffix -i. These findings confirm the importance of morphological changes in conveying the relationship between subjects, objects, and events in language. In addition, this research validates previous findings, showing that applicative constructions in Sorkam Malay Dialect remain relevant to previous research in the context of applicative constructions in other languages.